1974
DOI: 10.1021/jf60196a011
|View full text |Cite
|
Sign up to set email alerts
|

.alpha.-Galactosidase activity of fungi on intestinal gas-forming peanut oligosaccharides

Abstract: and Rhizopus oligosporus, the two fungi which are used in the preparation of fermented peanut press cake (ontjom), and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…a fermented peanut product, is popular in Indonesia. Worthington [94] showed that fermentation with Neurospora sitophila removed raffinose oligosaccharides within 24 h and rendered the product considerably less flatulent.…”
Section: Etizymatic Actionmentioning
confidence: 99%
“…a fermented peanut product, is popular in Indonesia. Worthington [94] showed that fermentation with Neurospora sitophila removed raffinose oligosaccharides within 24 h and rendered the product considerably less flatulent.…”
Section: Etizymatic Actionmentioning
confidence: 99%
“…However, to date only a few α-galactosidases have been identified with such properties [15,[17][18][19] and have mainly been isolated from fungi [22][23][24][25]. As most of alphagalactosidases in the food industry are obtained from probiotic bacteria like bifido and lactic acid bacteria [16,17,19,21,22], and due to the fact that a large number of these are sensitive to gut proteases, the maximum activity of commercial α-galactosidases should be assured to the customer. To date, few studies have been carried out on α-galactosidase determination in dietary supplements [16][17][18]21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…As most of alphagalactosidases in the food industry are obtained from probiotic bacteria like bifido and lactic acid bacteria [16,17,19,21,22], and due to the fact that a large number of these are sensitive to gut proteases, the maximum activity of commercial α-galactosidases should be assured to the customer. To date, few studies have been carried out on α-galactosidase determination in dietary supplements [16][17][18]21,23,24]. Our investigations showed how to validate an assay for enzymatic activity evaluation using a simple spectrophotometric measurement at 420 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation